2011
DOI: 10.3171/2010.12.spine10472
|View full text |Cite
|
Sign up to set email alerts
|

Utility of minimum clinically important difference in assessing pain, disability, and health state after transforaminal lumbar interbody fusion for degenerative lumbar spondylolisthesis

Abstract: Object Outcome studies for spine surgery rely on patient-reported outcomes (PROs) to assess treatment effects. Commonly used health-related quality-of-life questionnaires include the following scales: back pain and leg pain visual analog scale (BP-VAS and LP-VAS); the Oswestry Disability Index (ODI); and the EuroQol-5D health survey (EQ-5D). A shortcoming of these questionnaires is that their numerical scores lack a direct meaning or clinical significance. Because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(202 citation statements)
references
References 26 publications
11
188
1
2
Order By: Relevance
“…In our study, 41 (53.9%) of 76 patients in Group C and 15 (45.4%) of 33 patients in Group D met this threshold. 6,[19][20][21] The number of patients who met the MCID for these instruments was greater in Group C than in Group D; however, there were no significant differences between the 2 groups. We could not assess how many patients met the MCID for the JOABPEQ in the 2 groups because no studies have assessed the MCID for the JOABPEQ in the lumbar degenerative diseases.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, 41 (53.9%) of 76 patients in Group C and 15 (45.4%) of 33 patients in Group D met this threshold. 6,[19][20][21] The number of patients who met the MCID for these instruments was greater in Group C than in Group D; however, there were no significant differences between the 2 groups. We could not assess how many patients met the MCID for the JOABPEQ in the 2 groups because no studies have assessed the MCID for the JOABPEQ in the lumbar degenerative diseases.…”
Section: Discussionmentioning
confidence: 72%
“…Although they were developed for degenerative spinal conditions other than SIJ and the effects of SIJF, the MCID for improvement in chronic back pain is approximately 20 % when measured by VAS [46] and that for ODI is approximately 13-15 points [47]. For EQ-5D, the MCID is less well defined, with changes of 0.15-0.46 reported [44,48]. Observed mean values in our study exceeded these MCID values for pain, ODI and EQ-5D, and response rates were markedly higher in the SIJF group compared to CM.…”
Section: Discussionmentioning
confidence: 99%
“…In a spine register, Solberg et al (2013) recently showed EQ-5D scores to lack specificity and sensitivity and that change corresponding to a level of 0.30 or more, indicates a success of the surgery. Parker et al (2011) have also shown the minimally clinical important difference in terms of EQ-5D to vary considerably in different conditions, so that no specific general value could be provided.…”
Section: The Euroqol 5-dimensions (Eq-5d)mentioning
confidence: 99%